A brief discussion of the magnetocaloric effect in thin films of manganite doped with chromium (2019)
In this work we report on the magnetocaloric effect of La2/3Ca1/3MnO3 (LCMO) and La2/3Ca1/3Mn0.94Cr0.06O3 (LCMCrO) manganite thin films grown by DC magnetron sputtering on LaAlO3 (100) substrates. X-ray diffraction shows that both doped and undoped films crystallize in the orthorhombic structure. Magnetic measurements show a decrease in both the Curie temperature, TC , and the saturation magnetization, MS , for the LCMCrO sample. The change in the magnetic entropy (?Sm ) was extracted from hysteresis loops at different temperatures around the ferromagnetic to paramagnetic transition, displaying a maximum of entropy change (?Sm ) max near TC in both films. Moreover, a shift in (?Sm ) max toward temperatures above TC with increasing magnetic field and a broadening of the entropy change curve were observed. Results of refrigeration cooling power show a lower efficiency for LCMCrO. In order to obtain a local insight into the magnetic interactions of these films, measurements of X-ray absorption spectroscopy and X-ray magnetic circular dichroism (XMCD) were performed. XMCD suggests that an antiferromagnetic coupling between Mn4+ - Mn3+ is favored with Cr3+ incorporation, which reduces the Mn L 2,3 XMCD signal and results in a decrease of MS and (?Sm ) max in LCMCrO films. © Published under licence by IOP Publishing Ltd.